Pelatihan pengembangan media pembelajaran daring menggunakan aplikasi Wix bagi sukarelawan Yayasan Rumah Impian Yogyakarta - Christmastuti Nur; Arida Susyetina; Rama E Darmayanan; Karolas Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This Community Service (PkM) aims to improve the knowledge and skills of the volunteers of Dream House Foundation in Yogyakarta in assisting street children during online learning which includes basic knowledge about Wix, steps to create, use, and develop Wix as an online learning medium. The activity is implemented using training methods as a form of Participatory Learning and Action, with the following implementation stages: (1) counseling on the benefits of Wix to support online learning (2) training and practice of creating Wix as online learning medium (3) FGD (4 ) creating Wix in groups (4) group work mentoring (5) result presentation and improvements (6) evaluation. The evaluation was started from the beginning of the activity with the criteria of the number of attendance, participation in each stage of the activity, and the presentation of Wix site design. The evaluation results show that 90% of the participants understand and can design Wix site to develop web-based online learning media. The creation of the Wix site according to the needs of the children in the assisted areas has referred to the Wix site developed by the facilitator team and supports the availability of online learning materials to study from home.